2011
DOI: 10.4093/dmj.2011.35.4.390
|View full text |Cite
|
Sign up to set email alerts
|

Association between Diabetic Polyneuropathy and Cardiovascular Complications in Type 2 Diabetic Patients

Abstract: Background: Diabetes mellitus is a major independent risk factor for cardiovascular disease (CVD), but high cardiovascular risk in diabetes mellitus patients is not completely explained by clustering traditional risk factors. Recently, associations between diabetic polyneuropathy (DPN) and macrovasculopathy have been suggested. We aimed to assess associations between DPN and cardiovascular complications in type 2 diabetic patients. Methods: Microvascular and cardiovascular complications were evaluated in 1,041… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The EURODIAB Prospective Complications Study reported that the presence of hypertension was associated with the development of DPN (Tesfaye et al 2005). Moreover, a strong association between DPN and cardiovascular disease has been reported in previous studies (Tesfaye et al 2005;Chung et al 2011). However, a relationship between DPN and diabetic nephropathy has not been consistently demonstrated.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The EURODIAB Prospective Complications Study reported that the presence of hypertension was associated with the development of DPN (Tesfaye et al 2005). Moreover, a strong association between DPN and cardiovascular disease has been reported in previous studies (Tesfaye et al 2005;Chung et al 2011). However, a relationship between DPN and diabetic nephropathy has not been consistently demonstrated.…”
Section: Discussionmentioning
confidence: 67%
“…; Chung et al. ). However, a relationship between DPN and diabetic nephropathy has not been consistently demonstrated.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, direct and straight comparisons will have to wait for the time being. Interestingly, some prospective works have proven a relationship between cardiovascular risk factors and distal symmetrical DPN development in type 1 15,22,23 and in type 2 diabetes mellitus 16,24,25 . Noteworthy, CVD at baseline was associated with double risk of neuropathy independently of cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…While the relationship between cardiac autonomic neuropathy and sudden death from CVD is demonstrated, 14 the evidence on the relationship between DPN and CVD has focused primarily on identifying its relationship with cardiovascular risk factors, 15 especially by cross-sectional studies. 16 Conversely, a recent publication has reported previous DPN being associated with a higher risk of presenting a first cardiovascular event. 17 To the best of our knowledge, there are no prospective studies focusing on the relationship between CVD presence and DPN development in T2DM patients.…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, glycemic control is still an important aspect of type 2 diabetes control, as poor glucose control contributes to increased complication rates, and complications from neuropathy (ie, foot ulcers and deformities) are exacerbated by poor glucose control. 30 Therefore, glycemic control can be a major area healthcare workers can focus on in clinical practice to improve outcomes of type 2 diabetes in LMICs such as Peru.…”
Section: Other Relevant Resultsmentioning
confidence: 99%